Massive left pulmonary artery aneurysm with a co-existing patent ductus arteriosus in a five-year-old female child: a case report - Javeria Khan,; Khan, Muhammad Mansoor; Zubair Brohi,; Mahwish Mahboob,; Sohail Khan Bangash, (Journal of the Pakistan Medical Association, 2024)
Pulmonary Artery Aneurysm (PAA), whether congenital or acquired, is a rare diagnostic finding compared to aortic aneurysms. There have been few cases where PAAs were documented as a complication of untreated Patent Ductus Arteriosus (PDA) due to long-standing Pulmonary Arterial Hypertension (PAH). However, it is quite rare for a case of PAA to be reported with co-existing PDA without PAH. This report highlights a case of a five-year-old girl who was presented with palpitations, easy fatigability, fever, cyanosis, and vomiting. A Chest X-ray showed moderate cardiomegaly. A PDA of 6 mm was diagnosed on Transthoracic Echocardiography (TTE) and a large cavity connected with LPA raised suspicion of a possible LPA aneurysm. A Chest CT scan confirmed the diagnosis of a saccular aneurysm, originating from the distal part of the main Left Pulmonary Artery (LPA) just proximal to the point of bifurcation into lobar branches, measuring 7.5 x 6.5 cm. ---Continue